ANTIPLASMODIAL ACTIVITY OF CRUDE EXTRACTS AND ESSENTIAL OIL OF LIPPIA MULTIFLORA IN MICE - Yoila David, Malann,; Gywa, Deme, Gideon; Esther, Daniel, Oluwatosin; Adetutu, Olanrewaju, Comfort; Segun, Olayanju, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The search for common and cheaper antimalarial drug in Nigeria cannot be over-emphasis considering the endemicity of the disease. Traditional medicines (whole plants or Parts of plants) have proven to have good antimalaria efficacy. The evaluation of the anti-malarial properties of the crude extract and essential oil of Lippia multiflora was carried out using standard procedure (curative) tests in laboratory mice. The result of the curative test showed 5% essential oil to have good antimalaria efficacy (75.00%) against Plasmodium berghei. Other experimental essential oils (20%, 10%) and crude extracts (100%, 50%, 25%) employed in this study all showed significant difference in parasiteamia percentage reduction when compared to the negative control group. All essential oils and crude extracts only reduced the parasiteamia in the mice but could not clear it all after termination of treatment. The constituents of the essential oils can therefore be isolated to test for the efficacy of each constitute